(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the frequency of osteoporosis and osteopenia among the general population of District Khuzdar, Baluchistan Pakistan. Methods: This was a cross-sectional study and the data was collected on “World Osteoporosis Day” 20th October 2019 during an awareness session arranged by Shaheed Baz Muhammad Kakar Foundation at Baluchistan University of Information Technology, Engineering and Management Sciences Khuzdar Campus. The bone mineral density of all participants fulfilling the inclusion criteria was determined with DMS PEGASUS SMART Bone Densitometer. The T-scores were measured based on the readings of each individual and further characterized as Normal (+1 to -1 Standard Deviations), Osteopenia (-1 to -2.5 Standard Deviations), and Osteoporosis (<-2.5 SD). Results: The total participants screened were 246 including 169(68.7%) males and 77(31.3%) females. The mean age was 37±7. Most(49.2%, n=121) participants were in the age range of 15 to 25 years. Majority (75.6%,n=186) of the participants had normal bone mineral density. Osteopenia was detected in 47(19.1%) and Osteoporosis in 13(5.3%) participants. Conclusion: Majority of our study participants had normal bone mineral density. However, osteopenia and osteoporosis was detected in good proportion of our study sample. Proper treatment can prevent insufficiency fractures in this osteoporotic fraction of our population.